Constraints Perceived by Members and Non-members About Women Dairy Cooperative Societies in Haryana (Indian Journal of Extension Education, 2012)
Livestock sector plays an important role in the national economy and social development of the country. Women constitute 71 per cent of the labour force in livestock sector as against 35 per cent in crop farming. Cooperatives have provided a platform to women to demonstrate their capabilities and competence through their activities. Cooperatives exclusively of women demonstrated that gender based interventions in its programmes planning not only increased income and employment, but also enhanced women’s status in family and society. To contribute particularly for women development in dairy sector, the Support to Training and Employment Programme (STEP), launched in 1987 by Ministry of Human Resource Development, Govt. of India aims to increase the self-reliance and autonomy of women by enhancing productivity and enabling them to take up income generation activities by sales of milk and use of income from it. The constraints perceived by the members of the WDCS viz., lack of loan facilities, lack of educational programme on dairy, lack of regular training programmes and lack of / Inadequate input supply. Whereas the nonmembers considered the Lack of / Inadequate input supply by WDCS, unavailability of technical personnel in time, lack of supply of free cattle feed mixtures and lack of regular supply of cattle medicines on free of cost.